Rapid methods for multi-level dissemination of neutralizing monoclonal antibody treatment for COVID-19 outpatients: designing for dissemination using the fit to context framework - Kwan, Bethany M.; Sobczak, Chelsea; Fish, Lindsey E.; Ginde, Adit A.; Grant, Gillian; Hamer, Mika K.; Leggott, Kyle; Owen, Vanessa; Reno, Jenna; Shrader, Justin; Whittington, Lindsey; Jones, Jenn L.; et al. (Frontiers in Public Health, 2024)
Introduction: Throughout the COVID-19 pandemic, there was an urgent need for the rapid and equitable translation of knowledge and effective treatments to reach vulnerable populations in response to the ever-shifting pandemic environment. The approval of neutralizing monoclonal antibodies (mAbs) for treatment of outpatient COVID-19 resulted in a need to rapidly design dissemination strategies to increase awareness and equitable access for community members and healthcare providers.Materials & Methods: We used the Fit to Context (F2C) Framework for Designing for Dissemination and Sustainability to a) design products such as messages and materials, and b) disseminate the products. We leveraged existing partnerships (e.g., community members, health system leaders, Regional Health Connectors, public health agencies, policymakers, and others) for activities including a) advising on contextual implementation challenges and opportunities; b) convening a stakeholder advisory panel; c) rapid feedback on product reach and impact; and d) serving as potential product adopters and distributors. We used concurrent data collection and co-design with rapid, iterative prototyping. We used real-world data to evaluate impact of D&I strategies on mAb use in Colorado.Results: Moving through the F2C Framework phases, we assessed mAb implementation and access barriers and facilitators, identified partner priorities, co-designed messages and materials for multiple audiences, and disseminated through audience-specific communication channels. An emphasis on equity led to tailoring materials to communities with lower health literacy, underand uninsured groups, Spanish-speaking communities, Native American communities, and rural areas. Dissemination messages, materials, and distribution strategies were updated frequently based on emerging data on COVID-19 treatment effectiveness and availability. Real-world data revealed more than 400% increase in both referrals and number of unique referring providers, with the greatest impact on underserved communities. This was accomplished in under 9 months.The Fit to Context Framework for Designing for Dissemination and Sustainability is a novel process framework that can inform a rapid, iterative dissemination strategy. The COVID-19 pandemic presented an opportunity to learn better ways to speed translation of evidence to practice and enhance equitable access to evidence-based care. The mAb Colorado project demonstrated the importance of having strong community-academic-public health partnerships and leveraging existing capacity to enhance adoption and reach.